2005
DOI: 10.1080/00365540410020767
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella diskitis in a 2-year old immunocompetent child

Abstract: Brucellosis is a disease of domestic and wild animals that is transmitted to humans and exists worldwide. We assessed the in vitro activity of moxifloxacin, ciprofloxacin, tetracycline, doxicycline, rifampin, streptomycin and trimethoprim-sulfamethoxazole (TMP/SMX) against 97 Brucella strains isolated from clinical samples, animals and dairy products in Mexico. Fluoroquinolones showed an antibacterial activity similar to that of tetracyclines (MIC(90) 0.5). Other drugs commonly used against brucellosis were le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 5 publications
7
15
1
Order By: Relevance
“…In the present study, amongst the tested antimicrobial agents, the MIC breakpoint for both tetracycline and doxycycline was found to be within the susceptible category and among the lowest recorded. This is in concordance with the previous reports [11, 22, 29]. Our MIC 50 and MIC 90 values were lower than previously being reported [21, 30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, amongst the tested antimicrobial agents, the MIC breakpoint for both tetracycline and doxycycline was found to be within the susceptible category and among the lowest recorded. This is in concordance with the previous reports [11, 22, 29]. Our MIC 50 and MIC 90 values were lower than previously being reported [21, 30].…”
Section: Discussionsupporting
confidence: 93%
“…Currently, tetracycline, rifampicin, trimethoprim-sulfamethoxazole/cotrimoxazole (SXT), streptomycin, and other aminoglycosides, separately or in combinations, are the most commonly used antimicrobial agents for brucellosis treatment. However, reduced susceptibility of the organisms to streptomycin [7], rifampicin [8, 9], and SXT [10, 11] has been reported recently warranting a proper investigation to assess the susceptibility pattern of the local isolates. The main aim of this study is to ascertain the most common species causing Brucella infection in Malaysia and to determine the susceptibility patterns of these clinical isolates against the commonly used antibiotic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Development of resistance to TMP/SMX to B. melitensis is an important issue. High rate of resistance to TMP/SMX has been reported from previous studies [17, 29]. In the present study, TMP/SMX was found to be susceptible with low MIC 50 (0.064 mg/L) and MIC 90 (0.25 mg/L) when compared to other antimicrobials which is consistent with previous reports [9, 13, 15].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, MICs of tetracycline (range - 0.032–0.5 mg/L) and doxycycline (range - 0.032–1 mg/L) are found to be in the susceptible category and MIC 50 and MIC 90 values are consistent with previous reports [9, 13, 15, 16]. However, increased MICs of doxycycline have been reported in a study from Mexico [17]. …”
Section: Discussionsupporting
confidence: 92%
“…This infectious aetiology is a rare condition in immunologically normal children and it is described mainly in the case reports 7 9–11. Also, in adults, it is a very rare condition presented in the literature in few retrospective studies 2 4 12…”
Section: Discussionmentioning
confidence: 99%